The association between polychlorinated dibenzo-p-dioxin exposure and cancer mortality in the general population: a cohort study - Lei Zheng; Xianli Zhang; Zhe Gao; Chunyu Zhong; Dezhi Qiu; Qing Yan (Frontiers Media S.A., 2024)
IntroductionEarlier research has indicated that being exposed to polychlorinated dibenzo-p-dioxins (PCDDs) in the workplace can heighten the likelihood of cancer-related deaths. Nevertheless, there is limited information available regarding the connection between PCDD exposure and the risk of cancer mortality in the general population (i.e., individuals not exposed to these substances through their occupation).MethodsThe National Health and Nutrition Examination Survey (NHANES) detected PCDDs in the general population, and the death data were recently updated as of December 31, 2019. We conducted Cox regression analysis and controlled for covariates including age, gender, ethnicity, educational attainment, physical activity, alcohol intake, NHANES survey period, BMI category, cotinine concentration, and household earnings.ResultsAfter accounting for confounding factors, the findings indicated that for each incremental rise of 1 log unit in 1,2,3,4,6,7,8,9-octachlorodibenzo-p-dioxin, there was a 76% rise in the likelihood of death from any cause, with a p value of 0.003. An increase of 1 log unit in the concentration of 1,2,3,4,6,7,8-heptachlorodibenzofuran could potentially lead to a 90% higher risk of cancer mortality, as indicated by a p value of 0.034 and a 95% confidence interval of 0.05-2.43. As the concentrations of 1,2,3,4,6,7,8-heptachlorodibenzofuran increased, the dose-response curve indicated a proportional rise in the risk of cancer mortality, accompanied by a linear p value of 0.044. The sensitivity analysis demonstrated that our findings were resilient.DiscussionIn the general population, an elevated risk of cancer mortality was observed in PCDDs due to the presence of 1,2,3,4,6,7,8-heptachlorodibenzofuran. Mechanistic research is required to further confirm it.